Can a renal nurse assess fluid status using ultrasound on the inferior vena cava? A cross-sectional interrater study - Steinwandel, U.; Gibson, N.; Towell, A.; Rippey, J.; Rosman, Johan (2018)
Introduction: Ultrasound of the inferior vena cava (IVC-US) has been used to estimate intravascular volume status and fluid removal during a hemodialysis session. Usually, renal nurses rely on other, imprecise methods to determine ultrafiltration. To date, no study has examined whether renal nurses can reliably perform ultrasound for volume assessment and for potential prevention of intradialytic hypotension. This pilot study aimed to determine if a renal nurse could master the skill of performing and correctly interpreting Point of Care Ultrasound on patients receiving hemodialysis. Methods: After receiving theoretical training and performing 100 training scans, a renal nurse performed 60 ultrasound scans on 10 patients. These were categorized by the nurse into hypovolemic, euvolemic, or hypervolemic through measurement of the maximal diameter and degree of collapse of the IVC. Scans were subsequently assessed for adequacy and quality by two sonologists, who were blinded to each other's and the nurse's results. Findings: The interrater reliability of 60 scans was good, with intraclass correlation 0.79 (95% confidence interval (CI) =0.63–0.87) and with a good interrater agreement for the following estimation of intravascular volume (Cohen's weighted Kappa ?w = 0.62), when comparing the nurse to an expert sonographer. Discussion: A renal nurse can reliably perform ultrasound of the IVC in hemodialysis patients, obtaining high quality scans for volume assessment of hemodialysis patients. This novel approach could be more routinely applied by other renal nurses to obtain objective measures of patient volume status in the dialysis setting.